Käfer aus Sibirien (Umgebung Novosibirsk) (Insecta: Coleoptera). - Schawaller, Wolfgang (Contributions to Entomology = Beiträge zur Entomologie, 1990)
Newly collected Coleoptera (356 species) from the Novosibirsk area in Western Siberia are listed. This material shows close correspondence with the Central European fauna. Different zoogeographical elements of the Novosibirsk fauna are treated and represented in maps.